A Comparative Study between the Traditional Banking and Mobile Phone Banking - Agyeman, George Aboagye; Amofah, Dennis Owusu; Manteaw, Joy Tenkoran (Growth, 2016)
Mobile phone banking is a new system of banking in the country and as such most of the network operators are now engaging and using it. Mobile phone banking is banking using mobile phone devices to transact businesses in the country. Today the internet is considered a mature medium, despite its relative newcomer status. The internet is more accessible to more people globally than any other medium except television. Most people now access the internet in Ghana than previously and due to this some firms are embarking on e-marketing to compete in the world. Now people can access the internet at any place and anywhere with the help of the network operators using their cell phones. Some of the objectives set for this research are to determine the type of documentations required before one can access his/her money and to identify where and when the recipients could access their monies. During the research it came out that customers need a form of identification and a secret code before they can access their monies and also the respondents are of the opinion that the mobile phone banking is easy and convenient and they spend less time accessing their monies. It was recommended that the network operators should educate the general public about the merits and demerits of the new technology as well as equipping their outlets with the state-of-the-art equipments.